Microstructure and properties of sintered Co-Cr-Mo alloy powder under different processing conditions - Zuraidawani Che Daud (School of Materials Engineering, University Malaysia Perlis, 2011)
This study has focused on the effect of sintering time and sintering temperature on the microstructure development and properties of sintered Co-Cr-Mo alloy powder, sintering mechanism and activation energy, and corrosion behaviour.